AUSTRALIAN FOREIGN POLICY TOWARDS INDONESIA RELATED EAST TIMOR 1975-1991 - Qunuri, Ririn; Pradjoko, Didik, Dr. (International Review of Humanities Studies, 2021)
This article will explain Australia's attitudes and views on the East Timor issue which caused conflict with Indonesia. But on the other hand, Australia cannot ignore Indonesia's interests in East Timor. In 1978, Australia recognized East Timor "de facto" as part of Indonesia. Then, the question arises why Australia supports the integration of East Timor with Indonesia. What are the underlying interests. The Timor Gap Treaty was ratified on 11 December 1989, strengthening Indonesia's position with Australia. Indonesia is considered more accommodating when compared to Portugal in the matter of maritime boundaries in the Timor Sea region. Indonesia is the most important neighbor country for Australia. In terms of Australian defense, the Indonesian archipelago is a stronghold in northern Australia. This is based on Australia's interest in regional security free from the intervention of other hostile countries. Therefore, the importance of efforts to create government stability in Indonesia. The purpose of this study is to determine the dynamics of Australian foreign policy as seen from the Australian security and defense framework in looking at the East Timor issue. In addition, this research will discuss the Opposition to the Balibo Declaration and the Indonesian military intervention in East Timor which invites Australia's ambiguous attitude in addressing the integration of East Timor with Indonesia. Even though it was always at odds with Indonesia, Australia continued to prioritize its national interests in dealing with Indonesia.